Transtextuality, Transmediality, and Paratranslation - Yuste Frías, José; Ferreiro Vázquez, Óscar (Íkala, Revista de Lenguaje y Cultura, 2025)
The term “transmedia” refers to the notion of transmediality to build —by means of translating texts and paratranslating paratexts— multilingual and multicultural realities, structured around distinct and varied transtextual relations between different digital formats. Drawing from the translational and paratranslational roles of Gérard Genette’s five transtextuality types —intertextuality, paratextuality, hypertextuality, metatextuality, and architextuality— in the transmedia universe, this theoretical article builds a new and renewed framework to recap these five transtextual relation types in translation, and inquires, based on new theoretical, didactic, and professional perspectives of paratranslation, the theoretically and ideologically legitimized use of the term “transmediality” in the field of translation. Accurately understanding and interpreting transtextuality and transmediality in actual translation commissions in the professional market is essential to translating texts and paratranslating non-verbal forms, which are always present in transtextual relations, which are as a result of multimodal and inter-semiotic translation. These are present in transmedial communication and production as a subproduct of the new digital adaptation modalities.